PENGEMBANGAN POTENSI DAN PEMBERDAYAAN MASYARAKAT DI BIDANG PERTANIAN UNTUK MENINGKATKAN KETAHANAN PANGAN DI DESA DURIAN KECAMATAN JANAPRIA - Mega Permata Anjany, baiq; Jumania, Jumania; Evilia, Witri; Junandar, Ferli; Ibnu Ma`ad, Ahmad; Iskasari, Elna; Najib, Najib; Almasih, Kevin; Apriana, Apriana (Universitas Mataram, 2025)
The development of potential and community empowerment in the agricultural sector in Durian Village is very important to improve food security. This empowerment aims to enable the community to manage natural resources optimally, increase agricultural productivity, and in turn can create better economic sustainability. This empowerment also includes increasing the capacity of farmers in the use of agricultural technology, with the aim of implementing the concept of food security to form community food processing. The work program is implemented with a methodology, namely (1) making irrigation access wheels (2) socialization of food security and processing (3) the influence of gadgets on early childhood. The results obtained are the results of this socialization showing that the community is quite enthusiastic about utilizing water wheels as an alternative socialization in meeting energy and irrigation needs, with this socialization it is hoped that the community can better understand the importance of utilizing water resources wisely and sustainably through water wheel technology. In addition, in terms of food security and processing, 3 real follow-ups of food security and processing were produced, namely (1) the release of 20,000 tilapia seeds (2) the distribution and planting of 1200 chili, tomato, and cabbage seeds (3) the manufacture of cassava rengginang UMKM products. And it can be concluded from the goal of increasing economic welfare, as well as maintaining economic balance. With a good understanding, the community can use natural resources efficiently without damaging the environment.